Exceeding the 30 Percent Quota: Women's Strategic Participation in Election Monitoring at the Denpasar Election Supervisory Agency (BAWASLU) - Anak Agung Gede Ananta Wijaya Sahadewa; Kadek Nadya Pramita Sari Sari (Mahadi: Indonesia Journal of Law, 2026)
This study aims to analyze in depth the role and contribution of women in the supervision process of regional head elections (Pilkada) in Denpasar City, with a focus on their level of involvement in the Denpasar City Election Supervisory Agency (Bawaslu). This study uses an empirical juridical method with a descriptive, qualitative approach, employing direct observation, document analysis, and in-depth interviews with Ni Wayan Eka Lestari, A.Ma as Coordinator of the Human Resources, Organization, and Training Division of Bawaslu Denpasar. The results of the study show that women's participation in election supervisory institutions has shown significant progress, with the composition of Bawaslu Denpasar membership meeting and even exceeding the 30% quota for women's representation, with two of the five commissioners and most of the secretariat staff being women. Women have proven to make a real contribution to maintaining the integrity of the regional elections, particularly through their meticulousness in data verification, their ability to communicate empathetically, and their sensitivity in resolving potential conflicts in the field. However, this study also found several obstacles, such as the double burden of domestic and public responsibilities, as well as the strong influence of patriarchal culture, which still places women in a subordinate position. Therefore, this study recommends strengthening affirmative policies, increasing women's resource capacity, and creating a more equitable and inclusive work environment to encourage women's continued participation in election monitoring.